Réponses

2013-02-28T19:23:15+01:00

A = 9(4x²-4x+1) - 22(2x-1)(3x+5)

   = 9[(2x)²-2 x 2x x 1 +1²] - 22(2x - 1)(3x + 5)

   = 9(2x - 1)² - 22(2x - 1)(3x + 5)

   = (2x - 1) [(9(2x - 1) - 22(3x + 1)

   = (2x - 1)[ 18x - 9 - 66x -22]

   = (2x - 1)(-48x -31)

 

B = (x + 3)(11 - 5x) + x² -9

    = (x + 3)(11 - 5x) + (x - 3)(x + 3)

    = (x + 3) [(11 + 5x) + (x + 3)]

    = (x + 3) (11 + 5x + x + 3)

    = (x + 3)(-4x + 8)

 

C = 3x(9x² + 42x + 49) - 2x(4x - 1)(3x +7)

    = 3x(3x + 7)² - 2x(4x - 1)(3x + 7)

    = (3x+7)[3x(3x + 7) - 2x(4x - 1)

    = (3x + 7)[9x² + 21x - 8x² + 2x]

    = (3x + 7) (x² +23x)

    = (3x + 7)(x(x + 23))

 

D = 196 - 4x² - 2(5x + 9)(14 -2x)

    = 14² -(2x)² - 2(5x + 9)(14 - 2x)

    = (14 - 2x)(14 + 2x) - 2(5x + 9)(14 - 2x)

    = (14 - 2x)[(14 + 2x) - 2(5x +9))

    = (14 - 2x) (14 + 2x -10x -10)

    = (14 - 2x)( -8x -4)

 

Alors je veux bien t expliquer mais parle moi en privé :)